Herpetofauna of Paranapiacaba: expanding our knowledge on a historical region in the Atlantic forest of southeastern Brazil - Trevine, Vivian; Forlani, Maurício C.; Haddad, Célio F. B. [UNESP]; Zaher, Hussam (Sociedade Brasileira de Zoologia, 2014)
The largest area of preserved Atlantic forest is located in the southern portion of Brazil. The region of Paranapiacaba is depicted in Brazilian zoological studies as one of the first and most intensely sampled areas of the state of São Paulo.We provide a concise list of reptiles and amphibians from the Paranapiacaba Municipal Park. It represents the first comprehensive survey of the group in the area. We recorded 136 species of reptiles and amphibians from field surveys, museum collections and the literature. The anuran diversity of Paranapiacaba is greater than that of Estação Ecológica de Boracéia, which has been considered the most distinctive areas in São Paulo in terms of amphibian diversity. The rich history of herpetological research in the region, including the occurrence of the two most threatened species in Brazil, converts the area to an important conservation landmark for the Brazilian herpetofauna.
Keywords: Anuran conservation; conservation unit; herpetofaunal diversity; historical records; São Paulo state